The millipede genus Klimakodesmus Carl, 1932, with the description of a new species from Kerala state, southern India (Diplopoda, Polydesmida, Pyrgodesmidae) - Aswathy, Mathilakath Dasan; Golovatch, Sergei I.; Sudhikumar, Ambalaparambil Vasu (Zootaxa, 2021)
Klimakodesmus Carl, 1932 is briefly redescribed, rediagnosed, and shown to be an oligotypic genus endemic to southern India and distinct from the particularly similar genus Pyrgodesmus Pocock, 1892, monobasic and endemic to Sri Lanka, by several important features of peripheral and, especially, gonopodal structure. A new species, Klimakodesmus bilobocaudatus sp. nov., is described from Kerala state, India, differing from the sole accepted, and type species K. gravelyi Carl, 1932, from Tamil Nadu state, primarily by the laterally trilobate paraterga, the caudally more deeply bilobate mid-dorsal keel on ring 19, and certain minor details of the gonopodal structure.